ISU SOSIOSAINTIFIK DALAM PEMBELAJARAN KIMIA : SYSTEMATIC LITERATURE REVIEW - Alya Salsa Nabila; Heppy Okmarisa; Tarisa Humaira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to assess the use of socioscientific issues (SSI) in chemistry learning at the SMA/MA level based on a systematic literature analysis. Using the PRISMA method, 25 articles published between 2019 and 2024 were analyzed to evaluate trends, learning materials, and the impact of SSI implementation in the context of chemistry education. The analysis showed that organic chemistry and environmental chemistry had the highest proportion of use (16%), followed by acid-base, polymers, electrolyte solutions, and thermochemistry. The year 2022 became the peak of SSI-related publications with 7 articles, while 2023 showed a significant decline with only 1 article. The use of SSI is proven effective in improving learning relevance, student motivation, critical thinking skills, andenvironmental awareness. This research provides guidance for chemistry teachers to design SSI-based learning that is contextual, applicable, and meaningful